PENGUJIAN BLACKBOX PADA SISTEM PEMESANAN UNTUK SALES ORDER DI PT BUKIT MURIA JAYA BERBASIS EQUIVALENCE PARTITIONS - Muhammad Nurfathullah (Universitas Lampung, 2024)
This research aims to conduct blackbox testing on the sales order booking system at PT. BMJ based on the concept of equivalence partitions. The blackbox testing method is employed to assess the functionality of the system without considering its internal implementation. The study identifies representative equivalence partitions within the input and output domains of the sales order booking system and utilizes these partitions to design test cases. Through a series of tests, the system's performance is analyzed under various input conditions representing each partition. The testing results provide a better understanding of the system's reliability, identify potential defects, and offer recommendations for further improvement. This study contributes to enhancing the quality of the sales order booking system at PT. BMJ through a systematic and structured blackbox testing approach.